Light Emission from Single Self-decoupled Molecules in a Scanning Tunnelling Microscope - Rai, Vibhuti Narayan (Experimental Condensed Matter Physics, 2022)
In this work, a clear pathway is presented to achieve well-defined electronically decoupled chromophores from metallic leads without requiring additional insulating layers. To study such self-decoupled molecules, STM equipped with an efficient light detection setup has been used. Results show that the chromophores mounted on tripodal molecular platforms adsorbed on a gold surface present well-defined and efficient electroluminescence down to the single-molecule level.